Improvement of MTSTR Column Performance under Eccentric Loads. Issue 11 (18th August 2022) - Labibzadeh, Mojtaba; Jamalpour, Reza; Khajehdezfuly, Amin; Jing, Deng-Hu
ABSTRACT: The performance of a new type of concrete columns reinforced with multi-tied spiral transverse reinforcements called MTSTR columns has not yet been investigated and compared with other types of columns under eccentric loads. In this regard, three types of concrete columns, concrete-filled steel tube column (CFST), traditional concrete column (TCC) and MTSTR column were simulated in this study by nonlinear finite element (FE) method. The comparison between the load–moment interaction ( P -M) diagrams of these columns revealed that the MTSTR column is the weakest among the three column types in the tension-controlled region of the P -M diagram. An oriented comprehensive parametric study was carried out in order to detect the reason and overcome the above-mentioned shortcoming. Obtained results showed that utilization of more spirals with small diameters and vertical spacing placed near the sides of the cross-section instead of a few spirals with the large diameter and vertical spacing located in the central part of the cross-section of the column improves considerably the eccentric bearing capacity of the MTSTR columns.